2012
DOI: 10.1159/000337089
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Results with the MED-EL Fine Structure Processing Coding Strategy in Experienced Cochlear Implant Users

Abstract: Objectives: To assess the subjective and objective performance of the new fine structure processing strategy (FSP) compared to the previous generation coding strategies CIS+ and HDCIS. Methods: Forty-six adults with a minimum of 6 months of cochlear implant experience were included. CIS+, HDCIS and FSP were compared in speech perception tests in noise, pitch scaling and questionnaires. The randomized tests were performed acutely (interval 1) and again after 3 months of FSP experience (interval 3). The subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 46 publications
0
26
0
8
Order By: Relevance
“…Riss et al [21] found that there were no statistical significance differences whether FSP or CIS were used. Müller et al [22] compared FSP and HDCIS, and they showed that both performed equally in speech perception tests. Pitch scaling showed that FSP performed at least as well as HDCIS.…”
Section: Discussionmentioning
confidence: 99%
“…Riss et al [21] found that there were no statistical significance differences whether FSP or CIS were used. Müller et al [22] compared FSP and HDCIS, and they showed that both performed equally in speech perception tests. Pitch scaling showed that FSP performed at least as well as HDCIS.…”
Section: Discussionmentioning
confidence: 99%
“…In studies with larger subject groups, the effects of FSP can be measured after a relatively short period. Muller et al [6 ]studied the effect of FSP on monosyllable and vowel discrimination and sound quality in 46 experienced CI users. These subjects were followed up for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on acute or short-term effects of FSP did not find any improvement in speech perception [2,3]. When patients are followed up for a longer period of time, significant improvements in speech perception in quiet and in noise have been reported [4,5,6]. However, others reported no benefit of FSP even after 12 months of experience [7].…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to the degraded signal provided by the CI or by CI users' inability to discriminate or process all the information that is actually transmitted by the implant. Some advances in speech perception could be reached by newer coding strategies [3,4]. However, considering the different quality of electric representation of the acoustic environment with limited frequency representation provided by a CI, auditory effects on the phonetic and spectral characteristics of speech can be expected in CI users.…”
Section: Introductionmentioning
confidence: 99%